Arquitectura como um meio para a revitalização urbana. Projecto Estratégico para a Rua Teixeira de Vasconcelos, Amarante - Sara Mónica Seixas Gomes Leite (2017)
The present work thrives from a need of a reviewconcerning ways of seeing and thinking about currentcities, finding within the Architecture subject awork method based on the analysis of social, culturaland economic dynamics.The contemporary city, a stage of many sociologicaltransformations, has been under the devitalizationof its historical centre. This situation has put thepatrimony and the human and cultural essence thatdistinguishes and singles it at risk, and so, becauseof this, an urgent reflection about ways of interventionis required, with the will of giving back life tothe urban centre, waging in the economic revitalizationand in the increase of the population settlingpower of this area.As is specified in the Urban Regeneration ActionPlan of Amarante, the idea of a sustainable citycomes through the regeneration of existent urbanstructures, instead through urban sprawl. So, the urbanelement STREET as a sample for this essay waschosen. This choice came about due to the strongpotentiality that this urban space has in creating dynamics,exchanges and flows in the city. When streetsfunction well on the level of everyday experience, theyprovide opportunities for people to connect in a way thatno other public space can.For this reason, using the study case Rua Teixeirade Vasconcelos as part of Amarante's historical centre,an urban, social, cultural and economic studywill be presented that will help in the sketch of a cohesiveand diversified urban strategy, sustained inthe pre-existing dynamic and structure.Giving value to the punctual architecture interventionrole, two projects are developed, one aboutthe rethinking and treatment of a public space andanother about the programmatic use of a derelictbuilding located in the study area.From the strategy point of view, the perspective ofthe process of an urban revitalization in Amarante isprojected, to extend the rehabilitation action in timeand space.All this work has been combined by the knowledgeof strategies that had already been started, thatshare the same interest in the construction of actionand intervention methods in the city, both materialand immaterial, always bearing in mind an enlargedand extensive result throughout the city.In summary, understand Architecture as a meanto a urban revitalization project, implies working inseveral drawing and thinking scales of the urban reality,its knowledge and concerns.